World sugar outlook and the European policy - Ian Smith (Intereconomics, 1973)
Sugar has always been a highly political and controversial commodity, but never more so than at the present time. The uneasy rivalry between cane and beet sugar, the products of tropical and temperate countries respectively, is giving way to open conflict.
Keywords: 330; EC